Changes of nutrients and potentially toxic elements during hydrothermal carbonization of pig manure. (March 2020) - Song, Chengfang; Yuan, Wenqiao; Shan, Shengdao; Ma, Qi; Zhang, Haibo; Wang, Xudong; Niazi, Nabeel Khan; Wang, Hailong
Abstract: The effects of reaction temperature, residence time, sulfuric acid and potassium hydroxide on the total concentration and speciation of N and P, potentially toxic elements (salts and metal elements) of pig manure during its hydrothermal carbonization (HTC) were investigated. Concentrations of Cl, K, Na and Mg in the hydrochars were much lower but total N, P and nitrate-nitrogen (NO3 − -N) contents were significantly higher than in untreated pig manure. The acid-extractable fractions of Cu and Zn in hydrochars were 0.03–0.63 and 0.17–0.66 times lower than those in pig manure and decreased significantly with increasing reaction temperature. The addition of sulfuric acid (H2SO4) or potassium hydroxide (KOH) in HTC reduced the contents of P, Ca, Mg, Cl and heavy metal elements (HMEs) in hydrochars, and the removal rates of Cu and Zn were up to 55% and 59%, respectively. Overall, the rapid treatment of pig manure by HTC reduced the harm of salts and HMEs, and effectively recovered the nutrients in pig manure. The HTC under alkaline conditions was desirable for optimizing the main elemental composition of the hydrochars. Highlights: Pig manure total N, P and nitrate-N were significantly enriched by HTC. Pig manure salt and metal environmental risks were reduced by HTC. Acid-extractable [Cu] and [Zn] in HC200 were only 0.03 and 0.17 times those in pig manure. Alkaline hydrolysis at 180 °C optimized the main elemental composition of the hydrochars.